2019
DOI: 10.3390/su12010258
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and Key Factors of Success for ISO 14001 Certification: Evidence from an Emerging Arab Gulf Country

Abstract: The objectives of this research were: (1) To examine the outcomes and key factors of success (KFS) related to ISO 14001 certification, (2) to compare and contrast these in private organizations (PRIVOs) and public organizations (PUBOs), and (3) in the under-explored context of an Arab Gulf country with an emerging economy: The United Arab Emirates. We used an exploratory, qualitative research approach, based on semi-structured interviews with the environmental managers of 14 UAE organizations from the private … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 54 publications
(160 reference statements)
0
15
0
1
Order By: Relevance
“…This redesign of technical processes often leads firms to operate with higher efficiency (Darnall & Edwards, 2006; De Jong, Paulraj, & Blome, 2014; Schoenherr, 2012). For instance, empirical evidence has shown that ISO 14000 adoption results in enhanced workforce productivity (Ozusaglam, Robin, & Wong, 2018; Treacy, Humphreys, McIvor, & Lo, 2019), lower required time for manufacturing (Melnyk, Sroufe, & Calantone, 2003), more efficient investments in R&D because of better management of resources (He & Shen, 2019), lower operating costs (Lo, Yeung, & Cheng, 2012; Treacy, Humphreys, McIvor, & Lo, 2019), and better use of materials and energy (Waxin, Knuteson, & Bartholomew, 2020).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…This redesign of technical processes often leads firms to operate with higher efficiency (Darnall & Edwards, 2006; De Jong, Paulraj, & Blome, 2014; Schoenherr, 2012). For instance, empirical evidence has shown that ISO 14000 adoption results in enhanced workforce productivity (Ozusaglam, Robin, & Wong, 2018; Treacy, Humphreys, McIvor, & Lo, 2019), lower required time for manufacturing (Melnyk, Sroufe, & Calantone, 2003), more efficient investments in R&D because of better management of resources (He & Shen, 2019), lower operating costs (Lo, Yeung, & Cheng, 2012; Treacy, Humphreys, McIvor, & Lo, 2019), and better use of materials and energy (Waxin, Knuteson, & Bartholomew, 2020).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…For example, ISO 9001 identifies customers' needs and enables the quality policy to be achieved [1]. One widely adopted ISO standard is ISO 14001, which specifies particular environment goals and improves environment performance [2]. Furthermore, governments and social organizations have established various quality awards to identify firms that implemented an effective quality management system [3].…”
Section: Introductionmentioning
confidence: 99%
“…Companies are becoming more competitive as they improve their company image and stakeholder relations [41]. According to Waxin et al [42], by reducing resource consumption and implementing better waste management, companies certified by EMS can increase their profits. We have chosen ISO 14001 as the reference model because it includes the basic elements of any proper EMS; it is an international EMS standard, and it is being accepted more and more widely throughout the world as the EMS standard.…”
Section: Ems Iso 14001mentioning
confidence: 99%